Hubungan antara Self-Control dengan Perilaku Disiplin Siswa Kelas XI di SMA Negeri 1 Kuta Utara Badung Tahun 2026 - Ni Kadek Sindi Widyandari; Roro Dwi Umi Badriyah; I Wayan Juliawan (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aimed to determine the relationship between self-control and the disciplinary behavior of eleventh-grade students at SMA Negeri 1 Kuta Utara, Badung Regency, in 2026. The study employed a quantitative approach with a correlational research design. The population consisted of 396 eleventh-grade students, and a sample of 199 students was selected using proportional random sampling. Data were collected through self-control and disciplinary behavior questionnaires that had been tested for validity and reliability. Data analysis was conducted using normality testing, linearity testing, and Spearman Rank correlation analysis. The results revealed a correlation coefficient of 0.022 with a significance value of 0.762 (p > 0.05). These findings indicate that there is no significant relationship between self-control and the disciplinary behavior of eleventh-grade students at SMA Negeri 1 Kuta Utara, Badung Regency, in 2026. Therefore, the alternative hypothesis was rejected, while the null hypothesis was accepted. The findings suggest that students' disciplinary behavior may be influenced by factors other than self-control, such as family, school, and social environmental factors.